Structural Characteristics Of Verb Phraseological Units - Usmonova Umidakhon Hamzakhon kizi (International Journal Of Literature And Languages, 2026)
This article is devoted to a comparative structural-semantic and linguocultural analysis of verbal phraseological units in Uzbek, Russian, and English. The primary aim of the study is to identify the dominant structural models of verbal phraseological units, examine their component composition, and determine their degree of grammatical stability. The research employs structural-semantic analysis, comparative-typological, descriptive, and contextual methods. The findings demonstrate that verbal phraseological units in each language are characterized by language-specific structural patterns, multi-layered semantics, and a high degree of cultural markedness.